On the Measurement of Solvency of Insurance Companies: Recent Developments that will Alter Methods Adopted in Emerging Markets - Thorburn, Craig (World Bank, Washington, D.C., 2013)
Solvency-both as an economic requirement in the market and as a regulatory and supervisory tool-is critical to all insurance markets. Current market conditions, coupled with expected institutional changes, will place particular burdens on emerging and developing markets. Institutional solvency, effective risk management within companies, effective supervisory oversight, and the development of market disciplines are all linked. The author proposes that the effective implementation of the emerging regime needs a careful and diligent phased process of capacity-building. The first priorities are identified as a strong supervisor, a basic solvency margin requirement, and the initiation of efforts to gather appropriate data sets. This can be followed by advancing development of more sophisticated solvency regulation, increased use of technical expertise, and increased use of market disciplines as the community and financial markets become more able to exercise such discipline.